In the middle of the COVID-19 outbreak: early practical guidelines for psychosocial aspects of covid-19 in East Java, Indonesia (2020)
Objective: It is generally recognized that psychosocial interventions are an essential component in dealing with the COVID-19 outbreak. Research focusing on the handling of psychosocial conditions in the COVID-19 outbreak seems sparse. After reviewing several scholarly articles, we recommend several things that can be used as a basis for developing practical guidelines for handling psychosocial problems, especially in East Java Province, Indonesia. Method: Development of practical guidelines for first-hand response and early treatment of psychosocial aspects of COVID-19 in East Java Province, Indonesia, based on the recommendations of 14 articles related to COVID-19 psychosocial handling was carried out. Results: Some evidence strongly supports the need for knowledge about the stages of COVID-19, understanding of psychosocial responses, understanding of psychosocial interventions, and availability of hotline services in psychosocial interventions at each stage of the COVID-19 outbreak. Conclusion: It is important to provide practical guidance for the early management of psychosocial aspects of the innovative COVID-19 in providing more comprehensive care. There is strong evidence of the need for practical guidance on initial handling of the psychosocial aspects of COVID-19 for the community, especially in Indonesia's East Java Province.